The importance of adequate nutrition in preventing Alzheimer disease (Research, Society and Development, 2025)
Alzheimer's disease is a progressive neurodegenerative condition that affects memory, thinking, and behavior. Proper nutrition has been identified as an important factor in maintaining brain health and preventing Alzheimer's. This study aimed to evaluate how proper nutrition can help prevent Alzheimer's disease by investigating which nutrients and dietary patterns are most effective in reducing the risk of developing the disease. The study was of a review and exploratory nature, reviewing the available scientific literature on the relationship between nutrition and Alzheimer's disease. A narrative literature review approach was used, analyzing recent articles and research on the influence of different nutrients and diets on brain health and Alzheimer's prevention. Studies have shown that nutrition is essential for promoting health and preventing aging-related diseases, especially neurodegenerative diseases such as Alzheimer's. With increasing life expectancy, the incidence of dementia is growing, requiring effective strategies. Diets rich in antioxidants, vitamins, and essential fatty acids, such as the Mediterranean diet, have been shown to protect against cognitive decline and positively influence epigenetic mechanisms, activating beneficial genes and silencing harmful ones. In this context, nutritionists play an essential role in acting preventively and therapeutically, identifying the nutritional needs of the elderly and promoting interventions that preserve functionality and cognition.